2013
DOI: 10.5812/traumamon.7951
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Pin and Plaster Versus Locking Plate in Distal Radius Intraarticular Fractures

Abstract: BackgroundDistal radius fractures are among the most prevalent fractures predictive of probable occurrence of other osteoporotic fractures. They are treated via a variety of methods, but the best treatment has not been defined yet.ObjectivesThis study was performed to compare the results of open reduction and internal fixation with locking plates versus the pin and plaster method.Materials and MethodsIn this prospective study, 114 patients aged 40 to 60 years with Fernandez type III fracture referring to Imam-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, dorsal plating is associated with extensor tendon complications, which allowed the volar locking plating approach to gain more acceptance 43 . On the other hand, plaster fixation can be tailored according to the fracture features and is suitable for all types of fracture fixation and external fixation, with little adverse reactions 44 . Plaster bandage is a commonly used material in plaster fixation, containing dehydrated calcium sulfate powder that can be easily molded after absorbing water and gradually crystallizes to harden in a short time to maintain the original shape 45 .…”
Section: Discussionmentioning
confidence: 99%
“…However, dorsal plating is associated with extensor tendon complications, which allowed the volar locking plating approach to gain more acceptance 43 . On the other hand, plaster fixation can be tailored according to the fracture features and is suitable for all types of fracture fixation and external fixation, with little adverse reactions 44 . Plaster bandage is a commonly used material in plaster fixation, containing dehydrated calcium sulfate powder that can be easily molded after absorbing water and gradually crystallizes to harden in a short time to maintain the original shape 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Iranian surgeons have announced several novel techniques in the literature in order to replace the Western instruments with domestic instruments or alternative techniques to provide better outcomes in various clinical cases, which have been always challenging for all physicians worldwide, such as humerus fracturs treatment, distal humerus bone graft, radius fractures, femoral fracturs, etc. [8][9][10][11][12][13]. In instance, an Iranian study carried out on patients who suffered complex distal humerus fracture, and authors used K-wires to reconstruct and restabilize the surface of the bone [11,14].…”
Section: Discussionmentioning
confidence: 99%
“…He, however, studied only the patients of less than 17 ( 16 ).Bahari-Kashani et al (2003) studied the intra-articular distal end radius fractures managed by pin and plaster or plating. They concluded that functional scoring, radiological indices, grip strength, and supination pronation were better in the plating group ( 17 ). Mardani et al compared the closed reduction with long-arm cast to closed reduction with PCP and found the latter as better option in terms of finger stiffness, but found some pin tract infections, which resolved uneventfully ( 18 ).…”
Section: Discussionmentioning
confidence: 99%